Effects of entering adulthood during a recession - Lisa Dettling (IZA World of Labor, 2016)
Current cohorts of young adults entered adulthood during an international labor and housing market crisis of a severity not experienced since the Great Depression. Concerns have arisen over the impacts on young adults' employment, income, wealth, and living arrangements, and about whether these young adults constitute a “scarred generation” that will suffer permanent contractions in financial well-being. If true, knowing the mechanisms through which young adults' finances have been affected has important implications for policy measures that could improve the financial well-being of today's young adults in the present and future.
Keywords: D14; E24; J13; 330; young adults; net worth; home ownership; unemployment; income; parental co-residence; Great Recession